Exploration on tribological behaviour of coumarin as copper rolling oil additive through surface characterization. (25th June 2020) - Tang, Huajie; Sun, Jianlin; Zhao, Zhangliang; He, Jiaqi
Abstract: Tribological performance of coumarin in copper rolling oil was studied by four-ball tests and cold rolling tests. Then a systemic investigation on surface topography and surface chemistry of rolled strips was performed by field emission scanning electron microscope (FE-SEM), laser scanning confocal microscopy (LSCM), x-ray diffraction (XRD), x-ray photoelectron spectroscopy (XPS) and Raman spectroscopy (Raman). Results showed that coumarin was a kind of potential lubrication additive. The average friction coefficient (AFC) and wear scar diameter (WSD) were reduced by 30.2% and 30.1%, respectively, when the optimum concentration of coumarin (2.0 wt%) was added in copper rolling oil. Meanwhile, as the formation of tribofilm during rolling process, the nonuniform deformation and adhesive wear were effectively inhibited. Thinner copper strips with fine surface quality were obtained. The surface average roughness (Sa) of rolled copper strips was reduced by up to 68.8%. Surface characterization showed that the carbonyl group in coumarin molecule connected to Cu atoms with its molecular plane vertical or tilted to the metal surface. Besides, thermal analysis disclosed that this tribofilm had negligible surface residuals, especially when coumarin concentration was lower than 3.0 wt%.